Conflict and Sustainability - Muscat, Robert J (Online Ethics Center, 2016)
This paper draws attention to an important aspect that has not gotten sufficient examination: How the substance of engineering programs and projects -- location, design, and effects on potential winners and losers -- can worsen, or ameliorate, hostilities in conflicted societies. In these situations, it is important that the engineers involved have the knowledge and tools needed for developing peace-building solutions.
Essay
Keywords: Climate Change; Ethics and Society; Governance; Human Rights; Law and Public Policy; Social and Political Conflict; Social Responsibility; Sustainability; Controversies